Supervision as Governance Instrument: Compliance and Accountability in PTKIN-BLU Indonesia - Irma Agustina; Zaki Sima Fashimado; Anitasari Anitasari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study investigates the supervision strategies employed by the Internal Supervisory Units (Satuan Pengawasan Internal/SPI) of four State Islamic Universities (Universitas Islam Negeri/UIN) operating under Public Service Agency (Badan Layanan Umum/BLU) status in Indonesia — hereinafter referred to as PTKIN-BLU Institutions. In 2024, a qualitative multiple-case study was carried out, involving in-depth interviews with Organ SPI at UIN Sunan Kalijaga Yogyakarta, UIN Raden Mas Said Surakarta, UIN Sayyid Ali Rahmatullah Tulungagung, and UIN Mataram. Drawing on Agency Theory, Stewardship Theory, the internal audit effectiveness literature, hybrid governance scholarship, and the Supervision–Compliance–Accountability (SCA) Framework developed herein, the study analyses five dimensions of internal supervision practice: reporting structure, evidence and documentation management, internal–external audit coordination, authority and execution governance, and strategic orientation. Findings show considerable differences between institutions across a governance maturity spectrum, from emphasis on compliance and accountability to preventive, developmental, and process-renewal strategies. UIN Sunan Kalijaga demonstrates the highest level of supervisory maturity, characterised by dual-principal reporting, dedicated archival infrastructure, and long-term institutional knowledge management. The study contributes an integrated empirical model of supervisory strategy for hybrid public service organisations. It offers practical recommendations to strengthen compliance and accountability in PTKIN-BLU institutions in developing-country contexts.